Optimization of replica exchange temperature ladder under the well-tempered ensemble - Liu, Yang (2020)
Selection of temperature sequence and bias factor is a critical step for the preparation of Parallel Tempering simulations in a Well-Tempered Ensemble (PT-WTE). We provide a scheme in this study to generate the temperature sequence and the corresponding bias factor optimally. The number of replicas for a complete coverage of a specific temperature range is adjustable in this scheme, while keeping the average acceptance probability (AAP) between neighboring replica-pairs unchanged. Two series of PT-WTE simulations were tested with the number of replicas as 16 and 8 respectively. This work leads to a better understanding and application of PT-WTE simulations.